People, place, and space: Theoretical and empirical reflections in studying urban open space (Geographical Journal of Nepal, 2021)
People, place, and space are the main domain of spatial research which is widely discussed in the geographic discipline. Geographers always focus on the meanings related to space and human interactions to explain people, place, and space. The concept was explained by Richard Harsthrone (1959), Fred E Lukermann (1964), David Harvey (1969), Henri Lefebvre (1974), Yi-fu Tuan (1974),  Edward Relph (1976) and Doreen Massey (2005), etc.  As a human geographer, Yi.fu Tuan has a great contribution to explain people-place relations and further explained by Relph, Massey, and other scholars. Grounding on the geographic research traditions, this paper presents the concept of people, place, and space reviewing the historiographical literatures and some empirical research studies on people-space relations. Theorists have argued that people and space are deep-rooted in studying place attachment creating people’s sense of place. People’s actions and behaviors create meaning through their individual and communal behaviors in that space where they live and interact. Moreover, theoretical perspectives argue that placemaking is always associated with the social and cultural dimensions of a society. Empirically, as an indigenous society, people from the core area of Kathmandu Metropolitan City (KMC) have been perceiving urban open space as a commonplace for social and cultural life activities whereas migrants’ people living in the newly growing settlements have been perceiving the open space as a place for recreation and social capital enhancement.